1997
DOI: 10.1073/pnas.94.22.12218
|View full text |Cite
|
Sign up to set email alerts
|

Design of compounds that increase the absorption of polar molecules

Abstract: Hydrophilic drugs are often poorly absorbed when administered orally. There has been considerable interest in the possibility of using absorption enhancers to promote absorption of polar molecules across membrane surfaces. The bile acids are one of the most widely investigated classes of absorption enhancers, but there is disagreement about what features of bile acid enhancers are responsible for their efficacy. We have designed a class of glycosylated bile acid derivatives to evaluate how increasing the hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…Such promotive action of bile acids is in correlation with their CMC values since the increase in the CMC leads to a decrease in the bile acid hydrophobicity and tendency to form micelles [9][10][11][12]. Bowe et al [9] suggested that an increased CMC means a lower membrane toxicity caused by the bile acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such promotive action of bile acids is in correlation with their CMC values since the increase in the CMC leads to a decrease in the bile acid hydrophobicity and tendency to form micelles [9][10][11][12]. Bowe et al [9] suggested that an increased CMC means a lower membrane toxicity caused by the bile acid.…”
Section: Introductionmentioning
confidence: 99%
“…Some bile acids can act as promoters of the transport of certain drugs through the cell membranes [9][10][11]. Such promotive action of bile acids is in correlation with their CMC values since the increase in the CMC leads to a decrease in the bile acid hydrophobicity and tendency to form micelles [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They are synthesized from cholesterol in the liver, from where they are carried via the bile duct to the small intestine, and return to the liver by absorption through the bile acid transporter [22,23]. The natural physicochemical properties and enterohepatic circulation of the bile acids suggest that these compounds could be used in the preparation of new drugs and formulations [24][25][26][27]. Using bile acid-based molecules, we developed a novel delivery agent that physically interacts with macromolecules to enable their oral absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In previous report, the active hydroxyl groups of flavonoid are generally glycosylated. Glycosylation increases hydrophilicity of a molecule, which in its turn impairs its interaction with cellular membranes and decreases its rate of absorption [38,39]. Moreover, the literature showed flavonoids also effective scavengers of peroxyl, superoxide, and peroxynitrite radicals [40].…”
Section: Resultsmentioning
confidence: 99%